(untitled) (BIRDEM Medical Journal, 2024)
Background: Lifestyle modification and physical activity are very important parts of diabetes management. Regular physical activity has been shown to improve glycemic control through increased insulin sensitivity and glucose tolerance. The aims of this study were to assess the glycemic level and pattern of physical activity among type 2 diabetic patients. Methods: This hospital-based cross-sectional study was carried out from July 2022 to October 2022 among 305 purposively recruited diabetic patients who came to receive care at the outpatient department of a teaching hospital in Dhaka, Bangladesh. A semi-structured questionnaire was used to describe socio-demographic information. Physical activity was assessed using the validated version of international physical activity questionnaire short form/ global physical activity questionnaire (IPAQ/GPAQ). Glycemic control was measured by HbA1C report done within 120 days of the interview. Blood pressure and body mass index were also measured at the time of inclusion. The physical activity level was categorized according to IPAQ scoring protocol as high level, moderate level and low level. Chi square test was carried out to determine the association of physical activity with type-2 DM, body mass index, glycemic and blood pressure control. Statistical significance was defined as p<0.05. Results: Among the participants only 0.3% had high level of physical activity. Moderate level of physical activity was found among 32.8% and low level of physical activity has been found among 66.9%. Among the participants 92.1% spent their time sitting during the weekdays while the time spent at home, at work, while doing course or class and during leisure activities. Among them 21% had the maximum 10 hours sitting time during the last week. The study showed that the persons who spent walking on at least 7 days has negative correlation with blood glycemic level and among them who spent time on sitting has positive correlation with blood glycemic level. Nearly two thirds of the respondents were female. The mean age was 53.09 ± 12.15 years. Majority of the participants were from urban area (69.83%) and the rest are from rural (21.31%) and sub urban (8.2%) area. There was no significant relation of level physical activity with any sociodemographic factors except monthly income, which showed low monthly income was associated with higher level of physical activity. Conclusion: The findings of our study focus on developing more awareness and providing facilities for physical activity to achieve the glycemic goal. BIRDEM Med J 2024; 14(3): 143-150